Desarrollo del proceso de atención de enfermería en paciente de 40 años con traumatismo craneoencefálico en Hospital General Quevedo - Peña Olaya, Erika Tatiana (2019)
Cranioencephalic trauma represents a socioeconomic problem for health services and in the family because of the high costs of care, because of the negative consequences it generates (temporary or permanent death and disability). It is also an issue of importance for doctors because they are forced to make diagnostic, therapeutic, and prognostic decisions, and sometimes they lead to legal conflicts; for the forensic expert, the valorization of seriousness, determination of the incapacities and legally establishes the criminalization of the different criminal modalities with the compensation of the injured. Among the main causes of trauma we will always find in the first instance the traffic accidents that will represents approximately 45% of the total causes followed by the falls with 33%. The symptoms of a traumatic brain injury will vary in relation to the size of the lesion and the structure of the affected brain. To determine the appropriate treatment for head trauma this will depend on the severity of this. In the nursing field, an important role is played by the application of the NANDA, NIC and NOC taxonomies, which allow the nursing professional to prepare a diagnosis in order to apply various care plans that will help improve the quality of life of the patient.